Project-Based Learning Implementation in Fundamental Chemistry Courses to Meet the 21st Century Learning Target - Subagia, I Wayan; Sudiatmika, Rai Sudiatmika (Jurnal Pendidikan Kimia Indonesia, 2023)
This research aimed at describing and explaining the implementation of project-based learning results in Fundamental Chemistry I course. This research was focused in achieving the 21st century learning target, namely students’ critical thinking, creativity, collaboration, and communication skills. This research was conducted in Chemistry Education Study Program of Undiksha involving 19 people of first year students in academic year 2022/2023. This research was qualitative research using descriptive method. The data were collected by utilizing observation and document analysis techniques and analyzed by using interpretive analysis. The research results reveal that: 1) Students are able to propose project titles critically and creatively in accordance with the given theme; 2) Students are able to plan and implement the project as well as report the project results in accordance with the given format; and 3) Students are able to communicate the project orally and written through classroom presentation and project report writing.